Uji serologi IgA karakter KNF EBNA1+VCA p-18 pada penderita keluhan kronis kepala leher - Camelia Herdini; Susanna Hutajulu; Sagung Rai Indrasari; Bambang Hariwiyanto; Jajah Fachiro; Sofia Mubarika; Jaap Middeldorp (PERHATI-KL, 2011)
Background: Nasopharyngeal carcinoma (NPC), especially the WHO type III, is correlated almost100% with Epstein Barr Virus (EBV) infection. This is indicated by high IgG and IgA antibody responsesagainst viral capsid antigen (VCA), early antigen (EA) and Epstein Barr Nuclear antigen (EBNA).Increased IgA NPC character antibodies may be detected 2-10 years before the presence of the tumor. Thisoccurs as a result of reactivation of EBV infection. Purpose: To find out the level of IgA NPC characterantibodies (EBNA1+VCA p-18) in patients with chronic symptoms in the head and neck and to determine whether the level of IgA can be used as an early sign of NPC. Methods: Observational analytic study on 218 patients with chronic symptoms in the head and neck. The research was conducted from July 2006to September 2010. ELISA technique was used as serology test for IgA (EBNA1+VCA p-18). Result: Samples were 90 males and 128 females. High level of IgA by ELISA was found in 28 males (31.1%) and 45 females (35.2%). The IgA level tended to increase with age. The most common chronic symptoms inthe head and neck were chronic rhinitis (15.6%) and nasal obstruction (7.8%). From all patients who hadhigh level of IgA, 3 patients (4.1%) were found positive of early stage NPC. Conclusion: More than 33%of patients with chronic symptoms of head and neck had high level of IgA NPC character. This methodcan be used as an early detection of NPC. Keywords: serology test in NPC, EBNA1, VCA p-18, NPC symptoms in head and neck Abstrak : Latar belakang: Karsinoma nasofaring (KNF) terutama tipe WHO III berkorelasi hampir 100%dengan infeksi Epstein Barr Virus (EBV). Hal ini ditunjukkan dengan tingginya respons antibodi IgGdan IgA terhadap viral capsid antigen (VCA), early antigen (EA) EBV serta antibodi Epstein BarrNuclear Antigen (EBNA). Kenaikan antibodi IgA dengan karakter KNF dapat terjadi 2-10 tahun sebelumterjadinya tumor. Hal ini terjadi sebagai akibat adanya reaktivasi infeksi EBV. Tujuan: Mengetahui kadarIgA karakter KNF (EBNA1+VCA p-18) pada penderita dengan gejala kronis di daerah kepala dan leherdan mengetahui apakah kadar IgA dapat digunakan sebagai tanda awal terjadinya KNF. Metode: Suatukajian analitik observasional terhadap 218 penderita dengan gejala kronis di daerah kepala dan leher.Penelitian ini dilakukan Juli 2006 sampai dengan September 2010. Pemeriksaan serologi IgA (EBNA1+VCA-p18)dilakukan denganteknik ELISA.Hasil:Terdapat90penderita laki-lakidan128 penderitaperempuan.HasiltesserologiIgAELISAdengankadartinggiditemukanpada28laki-laki(31,1%)dan45perempuan (35,2%). Kadar IgA cenderung meningkat pada peningkatan usia. Gejala kronis yangterbanyak dikeluhkan penderita adalah rinitis kronis, yaitu sebanyak 34 penderita (15,6%), diikuti denganobstruksi hidung sebanyak 17 penderita (7,8%). Pemeriksaan klinis lebih lanjut dari penderita yangmempunyai kadar IgA tinggi menunjukkan bahwa 3 penderita (4,1%) positif terkena kanker nasofaringstadium awal. __ Lebih dari 33% penderita dengan gejala kronis di daerah kepala dan lehermemiliki kadar IgA karakter KNF yang tinggi. Kadar IgA karakter KNF yang tinggi dapat digunakansebagai penanda awal kejadian KNF. Kata kunci: uji serologi KNF,EBNA1, VCA p-18, gejala KNF